Impacts of Omicron associated restrictions on vertical distributions of air pollution at a suburb site in Shanghai. (1st February 2023) - Zhang, Sanbao; Wang, Shanshan; Xue, Ruibin; Zhu, Jian; He, Siyu; Duan, Yusen; Huo, Juntao; Zhou, Bin
Abstract: To prevent the Omicron transmission, Shanghai government implemented varying degrees of restraint measures. This study provided a new insight into the responses of air pollution altitude dependence to restraint measures by conducting vertical observations at a suburb site in Shanghai. Based on the difference-in-differences (DiD) models that compare the results in 2021 (normal scenario) and 2022 (Omicron-based restriction), we evaluated the casual effects of restrictions on (i) nitrogen dioxide (NO2 ), (ii) aerosol (presented by aerosol extinction coefficient (AEC)), formaldehyde (HCHO) and glyoxal (CHOCHO) and (iii) ozone (O3 ), which are generally treaded as primary, multi-sources and secondary pollutants, respectively. The estimated results from 0.0 to 2.0 km show that the drop/rise induced by restrictions is greater below 1.0 km than that above 1.0 km. Averaged on vertical distributions, AEC, NO2, HCHO and CHOCHO during restrictions felled by 15.1% (0.12 km −1 ), 40.3% (1.65 ppbv), 10.0% (0.26 ppbv) and 28.6% (21.79 pptv), respectively, while O3 increased by 21.3% (18.12 μg/m 3 ). It indicates that restrictions induce significant drops in primary pollutants and enhancements in secondary pollutants. For multi-sources pollutants, the decline from primary sources can be partly offset by enhanced secondary productions, and the ratio of increased secondary sources to decreased primary sources can be elevated with height. The discrepancies of responses to restrictions are reflected in vertical distribution and types of air pollution, emphasizing the significance of vertical observations for diversified pollution. These finding can also be meaningful in the strategy development for prevention and control of air pollution. Graphical abstract: Image 1 Highlights: This study provided a new insight into the responses of air pollution altitude dependence to restraint measures by employing vertical observations. The difference-in differences model was applied to evaluate the casual effects of restrictions on different types of pollution. The decline of multi-sources pollutants from primary sources can be partly offset by enhanced secondary productions.